2018
DOI: 10.32674/jis.v8i1.166
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Acculturative Stress and Sociocultural Adaptation Among International Students at a Non-Metropolitan University

Abstract: This quantitative descriptive study analyzed levels of acculturative stress and sociocultural adaptation among international students at a non-metropolitan university in the United States related to certain demographic characteristics. Surveys were used to measure international students’ levels of acculturative stress and sociocultural adaptation, including five subscales of sociocultural adaptation (N = 413). Demographic questions included gender, age, and country of origin, length of stay in the United State… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 36 publications
(40 reference statements)
3
29
1
7
Order By: Relevance
“…Documented research findings concerning gender are mixed up and self-contradictory as well. For instance, according to Mahmood and Burke [52], male students reported higher acculturative stress than female students which challenges the finding that female students are more vulnerable to acculturative stress than males [53]. The Open Journal of Social Sciences present study, on the other hand, found no statistically significant association between gender and acculturative stress level and supported by several findings [8] [33].…”
Section: Association Between Sociodemographics and Acculturative Stresssupporting
confidence: 65%
“…Documented research findings concerning gender are mixed up and self-contradictory as well. For instance, according to Mahmood and Burke [52], male students reported higher acculturative stress than female students which challenges the finding that female students are more vulnerable to acculturative stress than males [53]. The Open Journal of Social Sciences present study, on the other hand, found no statistically significant association between gender and acculturative stress level and supported by several findings [8] [33].…”
Section: Association Between Sociodemographics and Acculturative Stresssupporting
confidence: 65%
“…Additionally, other studies pointed out that as intercultural contact continues to increase on college campuses, there is a continuing greater need to develop cultural competency and adaptation (Dorozhkin & Mazitova, 2008;Mahmood, 2014). In line with this, Ajzen and Madden (1986) suggest that the evaluation of an act (in this study, adaptation) is particularly useful in predicting intentions.…”
Section: Sociocultural and Psychological Adaptation At The Destinatiosupporting
confidence: 57%
“…Yeh and Inose found that, among international students studying in the United States from Europe, English fluency, social connectedness, and perceived social support satisfaction significantly mediated acculturative stress and provided a buffering effect. Mahmood (2014) found that among 413 non-urban international college students, participants who had English proficiency also had higher social adaptation and greater college satisfaction.…”
Section: Acculturative Stress and International College Studentsmentioning
confidence: 99%